Fabrication of 3D Nanostructures via AFM-Based Nanolithography - Lorenzo Vincenti; Paolo Pellegrino; Isabella Farella; Mariafrancesca Cascione; Valeria De Matteis; Fabio Quaranta; Rosaria Rinaldi (Proceedings)
The increasing use of nanomaterials in high-tech devices has posed an exciting challenge for the scientific community to develop new, easy, high-throughput nanofabrication approaches. Here, we present an easy AFM-based nanofabrication approach based on Static Plowing Lithography, with which we are able to realize patterns of 3D nanostructures on a thin PMMA layer. By coupling a wet etching process with ultrasound exposure, we effectively removed the polymer bulges at the nanostructure’s borders, increasing the quality of the patterned 3D nanostructures, and paving the way for their integration into lab-on-a-chip devices.